Practical KGC-Free Polynomial-Based Multiple Group Keys Agreement for IoT Health Care Systems. (22nd September 2021) - Cheng, Qi; Zhao, Zhuo; Hsu, Chingfang; Zhang, Maoyuan; Yang, Qing; Wu, Di
Abstract : Although nowadays lots of group key agreement schemes have been presented, most of these protocols generate a secret key for a single group. However, in the IoT HCS, more and more communications are involved in multiple groups and users can join multiple groups to communicate at the same time. Therefore, applying the conventional public-key-based one-at-a-time group key establishment protocols has heavy computational cost or suffer from security vulnerabilities. At the same time, in an IoT HCS, a trusted KGC is usually not available and so more flexible self-organized multigroup keys generation will be desired by all group members. In order to address this issue, a practical scheme for efficient and flexible KGC-free polynomial-based multigroup key establishments for IoT HCS is proposed. The proposed protocol can generate multiple group keys for all group members at once, instead of generating one key each time for a single group; more importantly, there is no need for a trusted KGC in the process of group keys establishment and each user can join multiple groups at the same time using only one reserved share. Meanwhile, the security of the proposed protocol is discussed in detail. Finally, we compare this protocol with the latest related group key distribution protocols in performance analysis. The results show that this efficient and flexible KGC-free polynomial-based multiple group keys establishment protocol is more suitable for practical group key agreement in IoT HCS.